Memoir of Pope's Chapel - Oglesby, Evelyn Bufford (Wilkes County, Georgia: Pope's Chapel First Methodist Church)
Memoir of Pope's Chapel by Evelyn Bufford Oglesby, October 4, 2020. Tignall, Georgia. United States.
1 electronic record (2 copies). 2 pages. Names: Archie Hayes; Evelyn Bufford Oglesby;
Keywords: Church history; Congregational churches; Homecoming; Methodist Church--Anniversaries, etc.; Methodists; Pope's Chapel United Methodist Church (Wilkes County, Ga.); United Methodist Church (U.S.); Wilkes County (Ga.); Georgia; Autobiographies